2014
DOI: 10.1136/archdischild-2013-305130
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported quality of life outcomes for children with serious congenital heart defects

Abstract: ObjectiveTo compare patient-reported, health-related quality of life (QoL) for children with serious congenital heart defects (CHDs) and unaffected classmates and to investigate the demographic and clinical factors influencing QoL.DesignRetrospective cohort study.SettingUK National Health Service.PatientsUK-wide cohort of children with serious CHDs aged 10–14 years requiring cardiac intervention in the first year of life in one of 17 UK paediatric cardiac surgical centres operating during 1992–1995. A comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
63
5
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(81 citation statements)
references
References 30 publications
9
63
5
4
Order By: Relevance
“…It is not surprising that Fontan survivors in this study have significantly lower QoL compared to their peers . Multiple prior reports have shown reduced QoL in patients with significant congenital heart diseases including patients with single ventricle physiology and Fontan . Our study finding of worse parent's perceptions of QoL status of their children compared to the children's perceptions after the Fontan procedure has been reported before .…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…It is not surprising that Fontan survivors in this study have significantly lower QoL compared to their peers . Multiple prior reports have shown reduced QoL in patients with significant congenital heart diseases including patients with single ventricle physiology and Fontan . Our study finding of worse parent's perceptions of QoL status of their children compared to the children's perceptions after the Fontan procedure has been reported before .…”
Section: Discussionsupporting
confidence: 62%
“…It is not surprising that Fontan survivors in this study have significantly lower QoL compared to their peers . Multiple prior reports have shown reduced QoL in patients with significant congenital heart diseases including patients with single ventricle physiology and Fontan .…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Although this review provides insight into long‐term mortality associated with CHD, we did not account for morbidity. Research suggests that quality of life is lower in those with CHD and that those who live with CHD can have morbidities such as endocarditis, cerebrovascular accidents, myocardial infarctions, and arrhythmias . The American Heart Association has also reported that children with CHD are at increased risk of developmental disorders .…”
Section: Discussionmentioning
confidence: 99%
“…Other factors, unrelated to cardiac status, may also affect physical activity in these patients . The quality of life for children with severe cardiovascular disease has been shown to be lower than that of healthy children . In Fontan patients, factors such as the type of pumping ventricle, number of surgical procedures and complications, age at completed Fontan circulation and arrhythmia have also been reported to influence health‐related quality of life .…”
Section: Introductionmentioning
confidence: 99%